2021
DOI: 10.3390/ph14101011
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Binding to NAP-Type Neuroprotective Peptides: Nuclear Magnetic Resonance Studies and Molecular Modeling

Abstract: Aggregation of amyloid-β peptides (Aβ) is a hallmark of Alzheimer’s disease (AD), which is affecting an increasing number of people. Hence, there is an urgent need to develop new pharmaceutical treatments which could be used to prevent the AD symptomatology. Activity-dependent neuroprotective protein (ADNP) was found to be deficient in AD, whereas NAP, an 8-amino-acid peptide (1NAPVSIPQ8) derived from ADNP, was shown to enhance cognitive function. The higher tendency of zinc ion to induce Aβ aggregation and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…A role as zincophore (Zn-binding compounds) seemed a possible function for ZDRPs because small molecules that chelate Zn have previously been observed in bacteria and fungi (45, 46). Since ESI-MS leads to disposition of Zn in the stainless steel capillary rendering it unsuitable to investigate metal-binding of ZDRPs (47), we instead employed the softer ionization method MALDI-TOF MS (48) to determine if ZDRPs contain bound Zn. Typical amino acids for Zn coordination are histidine and cysteine.…”
Section: Resultsmentioning
confidence: 99%
“…A role as zincophore (Zn-binding compounds) seemed a possible function for ZDRPs because small molecules that chelate Zn have previously been observed in bacteria and fungi (45, 46). Since ESI-MS leads to disposition of Zn in the stainless steel capillary rendering it unsuitable to investigate metal-binding of ZDRPs (47), we instead employed the softer ionization method MALDI-TOF MS (48) to determine if ZDRPs contain bound Zn. Typical amino acids for Zn coordination are histidine and cysteine.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to analyze how the aggregation processes of Aβ peptides are influenced by the action of extrinsic factors induced by hyperpyrexia to provide an overview of both, thermal and osmotic impact on AD patients. In addition, experimental investigations of transition metal ions linked to amyloid-beta monomers and oligomers pose challenges due to the disordered structure of Aβ, its fast aggregation, as well as solvent and paramagnetic effects (Strodel et al, 2019; Lupaescu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 40 cyclic peptide drugs derived from natural compounds have been authorized in clinical trials during the last few decades [ 26 ]. Recently, the molecular way in which neuroprotective NAP peptide ( 1 NAPVSIPQ 8 ) and its analog with acetylsalicylic acid can stabilize axonal microtubules has been proved [ 27 , 28 , 29 ]. It was also reported that the semi-elastic lipid nanoparticles significantly enhanced peptide oral availability and could be a viable future oral peptide delivery technology for peptide medicines [ 30 ].…”
Section: Introductionmentioning
confidence: 99%